Role Of Board Diversity In Investment Efficiency At Different Firm Life Cycle: Evidence From Mena Region - Al-Radaideh, Ibrahim Saleh Mohammad (2024)
The middle east and north africa (mena) region is confronted with formidable obstacles concerning inefficiency in investments and corporate governance (cg), specifically concerning on board diversity. It investigates the dynamic relationship between board diversity and firm investment efficiency across different stages of the firm life cycle (flc). While prior studies have explored the impact of board diversity on investment efficiency from a static perspective, this research incorporates the concept of flc stages to provide a more comprehensive understanding. The study is grounded in firm life cycle theory, which posits that agency costs associated with free cash flows (fcfs) are a recurring issue at specific stages in a firm's development. Board diversity, the independent variable, is measured using the entropy weighted board diversity index (ewbdi), incorporating nationality, women representation, and educational level. Investment efficiency, the dependent variable, is determined by the variance between actual and expected investment levels based on future growth opportunities. Flc stages, defined by fcf levels, act as the interacting variable and are categorized into four stages: introduction, growth, mature, and shake-out/decline.